9514 1404 393
Answer:
(x, y) = (10, 6)
Explanation:
Any of the usual methods work to solve this: elimination, substitution, graphing, matrix methods. For a "no-work" solution, I prefer a graphing calculator.
__
In the second equation, both x and y have coefficients of ±1, so substitution or elimination can be used with equal ease. Adding x to the second equation gives an expression for y that can be substituted in the first equation.
y = x -4
-3x +8(x -4) = 18
-3x +8x -32 = 18 . . . eliminate parentheses
5x = 50 . . . . . . . . . add 32, collect terms
x = 10 . . . . . . . . . . .divide by 5
y = 10 -4 = 6 . . . . . use the expression for y to find y
The solution is (x, y) = (10, 6).